Scalable Information Systems : 5th International Conference, INFOSCALE 2014, Seoul, South Korea, September 25-26, 2014, Revised Selected Papers - Jung, Jason J.; Badica, Costin; Kiss, Attila; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the International Conference on Scalable Information Systems, INFOSCALE 2014, held in September 2014 in Seoul, South Korea. The 9 revised full papers presented were carefully reviewed and selected from 14 submissions. The papers cover a wide range of topics such as scalable data analysis and big data applications.
Scalable Similarity Search for Big Data - Challenges and Research Objectives -- Content-based analytics of Diffusion on Social Big Data: a Case Study on Korean Telecommunication Companies -- Multi-modal Similarity Retrieval with a Shared Distributed Data Store -- An Efficient Approach for Complex Data Summarization -- A Novel Approach for Network Traffic Summarization -- Heart Disease Diagnosis Using Co-Clustering -- An Investigation of Scalable Anomaly Detection Techniques for a Large Network of Wi-Fi Hotspots -- Link Scheduling for Data Collection in Multichannel Wireless Sensor Networks A Design of Sensor Data Ontology for a Large Scale Crop Growth Environment System -- Real-Time Data Flow Language Processing System for Handling Streams of Data.
Keywords: Coding theory; Coding and Information Theory